The Healthy Waters science-based educational intervention programme: The potential of participatory approaches for developing and promoting students’ environmental citizenship - da Silva, Joel Bruno; Silva, Diogo; Barbosa, Marta Oliveira; Rodrigues, Mariana (JSSE - Journal of Social Science Education, 2024)
- Schools reproduce scientific knowledge uncritically. - Schools should provide educational opportunities for students’ action, reflection, and interaction. - Participatory approach allows students to expand their agency around climate change. - Participatory approach promotes students’ knowledge of their community’s environmental problems. Purpose: This paper explores the potential of students’ participation in the HW educational intervention programme based on participatory methodologies in promoting their environmental citizenship. Design/methodology/approach: Using a quasi-experimental design, 126 students were randomly assigned to the intervention and control groups and filled out questionnaires before and after the HW intervention to evaluate environmental citizenship dimensions. Findings: The psychometric properties of a 16-item instrument to measure youth environmental citizenship were validated. After the HW intervention, the students’ intervention group had a significant improvement in their sense of environmental efficacy. Research limitations/implications: The cross-sectional design of this study does not allow causal inferences to be made; further research should conduct longitudinal studies. Practical implications: Schools must promote educational experiences where students have opportunities for reflection and action in interaction in a climate of openness to dialogue and diversity with the involvement of different actors.